2021
DOI: 10.1038/s41598-021-00094-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stereopsis and vision-related quality of life following intravitreal ranibizumab injections for central retinal vein occlusion

Abstract: The study aimed to evaluate changes in stereopsis and vision-related quality of life (VR-QOL) in patients with central retinal vein occlusion (CRVO) following intravitreal ranibizumab injection (IVR) and investigate the relationship between stereopsis and VR-QOL. This study included 23 treatment-naïve patients with non-ischemic CRVO and 13 age-matched normal controls. Stereopsis, best-corrected visual acuity (BCVA), VR-QOL, and retinal microstructures were examined pre-treatment and 12 months post-treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to recent researches, binocular stereopsis is greatly impacted by monocular impairment in BCVA in various retinal disorders, including CRVO 27 , 28 , RRD 25 ,Macular hole 29 , and ERM 16 . Spearman correlation analysis in our results revealed a positive relationship between preoperative TST value and pre-BCVA, postoperative stereopsis and post-BCVA, as well as post-TNO value and pre-BCVA, which highlighted that is monocular visual acuity impairment closely linked to stereopsis.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent researches, binocular stereopsis is greatly impacted by monocular impairment in BCVA in various retinal disorders, including CRVO 27 , 28 , RRD 25 ,Macular hole 29 , and ERM 16 . Spearman correlation analysis in our results revealed a positive relationship between preoperative TST value and pre-BCVA, postoperative stereopsis and post-BCVA, as well as post-TNO value and pre-BCVA, which highlighted that is monocular visual acuity impairment closely linked to stereopsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to male-female differences in metabolism, lifestyle, and physical performance, this vast field of research has identified gender differences in response to therapeutic agents, diagnostic, and therapeutic interventions [16]. Furthermore, in the study by Okamoto et al, no differences in age and gender were observed between the groups [17].…”
Section: Discussionmentioning
confidence: 99%
“…The study by the author Korobelnik and associates showed significant functional and anatomical advantages of treatment with intravitreal drug applications in the eye. The endpoint of efficacy was patient who gained 15 or more letters in best-corrected visual acuity at week 24 of treatment, and the improvement achieved was maintained until week 52 of treatment [17].…”
Section: Discussionmentioning
confidence: 99%
“…The advent of anti-vascular endothelial growth factor (VEGF) therapy has improved the visual prognosis of patients with CRVO-CME [ 2 , 3 ]. However, even if CME resolves after treatment, some patients may not have satisfactory visual function due to metamorphopsia [ 4 ], decreased contrast sensitivity (CS) [ 5 ], and decreased stereopsis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Okamoto et al investigated stereopsis in patients with CRVO-CME after anti-VEGF therapy and reported that stereopsis improved after treatment. However, stereopsis remained worse than that in individuals without ocular disease and was associated with VR-QoL at baseline and after treatment [ 6 ]. Deramo et al reported that the best-corrected VA (BCVA) of the fellow eye was more related to VR-QOL than the VA of the affected eye in patients with CRVO-CME [ 11 ].…”
Section: Introductionmentioning
confidence: 99%